(untitled) (Research, Society and Development, 2020)
Evaluating the cervical sealing of composite resins FBF (Filtek bulk fill), BF (Beautifil flow), YF (Yflow SA) associated with a universal adhesive system in endodontically treated teeth. Materials and Methods: The used samples in the analysis of bacterial microleakage were autoclaved, filled within a laminar flow chambre and divided in 3 experimental groups (n =5) and (n=8) according with the restorative material: Filtek Bulk Fill Flow, Beautiful Flow e Yflow SA, positive control (n=3), negative control (n=3). The samples were inoculated with E. faecalis, every 7 days and the microleakage was daily evaluated for 60 days. The data were submitted to Fisher test and survival curve of Kaplan-Meyer, and to Long-Rank. All tests were realized through SPSS, version 23.0 (IBM SPSS Inc.), considering a significance level of 0.05. Results: 12,5% of FBF specimens presented bacterial microleakage from the 30th day, YF e BF presented the highest percentual of microleakage at 30 and 50 days respectively. BF presented highest percentual of microleakage at 50 days concluding the 60 days with 40% of viable species. The test of Log Rank did not revel a significative difference between the survival curves. Conclusion: FBF, BF and YF resins were incapable promoting a hermetical sealing of root canal system filling. Clinical significance: Promote the better sealing to avoid the paissage of bactéria, consequently establishing in endodontic long term treatment.